Trauma to the Skull: A Historical Perspective from the Southern Levant (4300BCE–1917CE). (11th July 2012) - Cohen, H.; Sarie, I.; Medlej, B.; Bocquentin, F.; Toledano, T.; Hershkovitz, I.; Slon, V.
ABSTRACT Background: Although the southern Levant is commonly perceived as having been a violent region throughout history, few studies have explored the pattern and intensity of skull trauma through time in the general population. The aim of this study is to follow changes in traumatic injury patterns in the southern Levant, over an extensive period of 6, 000 years. Methods: 783 archaeological skulls from the Tel Aviv University osteological collection were examined for evidence of trauma. The specimens were divided into three periods: Chalcolithic‐Bronze‐Iron Age (4300–520 BCE), Hellenistic‐Roman‐Byzantine Period (332 BCE‐640 CE), and Early and Late Arab Period (640–1917 CE). The characteristics of injury on each skull were recorded. Results: A high frequency (25%) of traumatic lesions to the skull was evident among historic populations of the southern Levant, a rate that did not fluctuate significantly over 6, 000 years. The most common pattern of trauma was minor circular depressed injuries. Most of the injuries were located on the parietal or frontal bones. Traumatic lesions were more frequent in males than in females, and in mature individuals than in adolescents and children, during all periods. Conclusions: The rate of trauma in the southern Levantine populations was shown to be considerably higher than in other archaeological populations worldwide. The fact that no significant differences in trauma rates were found over time implies that socio‐economical shifts (from agrarian to urban populations) had little impact on the local populations' aggressive behavior. In contrast, changes in type of injury, from blunt force trauma to sharp force trauma and eventually projectile trauma, reflects changes in weaponry over time. The accumulated characteristics of cranial trauma pattern (type, location, side, size, sex, age) suggest that most of the individuals studied were not engaged directly in warfare. Rather, most injuries seem to be due to blows given during interpersonal violent encounters. Copyright © 2012 John Wiley & Sons, Ltd.